Penerapan Cognitive Behaviour Therapy untuk Mengatasi Distorsi Kognitif pada Pelaku Pelecehan Seksual dengan Disabilitas Intelektual: Systematic Literature Review - Erizza Farizan Adani; Tirta Firdaus Nuryananda; Adiwignya Nugraha Widhi Harita (Jurnal Praba : Jurnal Rumpun Kesehatan Umum, 2024)
Knowledge about sexual harassment committed by males with intellectual disabilities remains limited, despite extensive research on offenders without disabilities. Evidence from the late 1990s suggests that Cognitive Behavioral Therapy (CBT) can be effective for this population, with adjustments for cognitive deficits. This study systematically reviews the application of CBT to address cognitive distortions in sexual offenders with intellectual disabilities. Data were sourced from Web of Science, PubMed, Scopus, ProQuest, Jstor, and Emerald Insight. Articles were assessed using QATFQS for quality and ROBINS-I for bias risk. Six studies involving 127 participants (ages 17–65 years) demonstrated that CBT effectively reduced cognitive distortions up to 12 months post-intervention. Success factors included the presentation of information, therapist engagement, participant motivation, prior experiences of sexual harassment, and autism spectrum diagnoses. Strengths included simplified CBT interventions, availability of manuals, and group implementation. Weaknesses involved reliance on core steps adapted from general sexual offender programs, limited manual accessibility, and a lack of control groups for evaluating intervention effectiveness.